Consumption of Raw Herbal Medicines Is Associated with Major Public Health Risks amongst Ugandans. (3rd June 2020) - Ssempijja, Fred; Iceland Kasozi, Keneth; Daniel Eze, Ejike; Tamale, Andrew; Ewuzie, Sylvia Anurika; Matama, Kevin; Ekou, Justine; Bogere, Paul; Mujinya, Regan; Musoke, Grace Henry; Atusiimirwe, Jovile Kasande; Zirintunda, Gerald; et al.
Abstract : Background . Community consumption of herbal plants in developing countries is a common practice, however, scarcity of information on their physiochemical composition is a major public health concern. In Uganda, Vernonia amygdalina is of interest in rural communities due to its therapeutical action on both bacterial and protozoal parasites, however no studies have been conducted to assess the heavy metal concentrations in traditional plants used in alternative medicine. The aim of the study was to establish concentrations of heavy metals in Vernonia amygdalina, model the estimated daily intake (EDI), and assess both the non-cancer-related health risk using the target hazard quotient (THQ), and the risk related to cancer through the incremental lifetime cancer risk (ILCR) for the Ugandan population. Methods . Leaves of Vernonia amygdalina were collected from 20 georeferenced villages and processed into powder in the laboratory using standard methods. These were then analyzed in the laboratory using an atomic absorption spectrometer for lead (Pb), chromium (Cr), copper (Cu), zinc (Zn), cobalt (Co), iron (Fe), cadmium (Cd), and nickel (Ni). Concentrations were compared against the World Health Organization (WHO) limits. The EDI, THQ, and ILCR were modelled and significance was measured at 95% confidence. Results . The study showed that mean ± SEM concentrations of heavy metals were highest in the order of Cr, 121.8 ± 4.291 ppm > Ni, 84.09 ± 2.725 ppm > Zn, 53.87 ± 2.277 ppm > Pb, 40.61 ± 3.891 ppm > Cu, 28.75 ± 2.202 ppm > Fe, 14.15 ± 0.7271 ppm > Co, 7.923 ± 0.7674 ppm > Cd, 0.1163 ± 0.005714 ppm. Concentrations of Pb, Cr, Zn, Co, and Ni were significantly higher than the WHO limits. The EDI was significantly higher in children than in adults, demonstrating an increased risk of toxicity in children. The THQ and ILCR were over 1000 times higher in all Ugandans, demonstrating the undesirable health risks following oral consumption of Vernonia amygdalina due to very high Cr and Ni toxicities, respectively. Conclusion . Consumption of raw Vernonia amygdalina was associated with a high carcinogenic risk, demonstrating a need to enact policies to promote physiochemical screening of herbal medicines used in developing countries against toxic compounds.